How to Write History? - Florian Coulmas (Storicamente)
78 years after the annihilation of Hiroshima, a G7 summit is scheduled to take place in Hiroshima. That both representatives/heirs of the victims and the victimisers of the first nuclear strike in human history will sit there around the same table is ample reason to reflect on the way this event is and should be remembered. Recalling some details of the bombings of Hiroshima and Nagasaki, this text recalls that the bombs did not, as is often thought, bring about Japan’s surrender in World War II and touches upon the contingency of history writing. It also recalls that it was common practice for a long time to refer to the “nuclear holocaust” and raises the question of whether and how present-day circumstances – in particular the fact that the 2023 G7 summit takes place in times of a war not anticipated by many just a year ago – do and should influence the perception and evaluation of past facts and thus their sedimentation in history.